2010
DOI: 10.1186/1476-072x-9-42
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of tick-borne encephalitis in counties of southern Germany, 2001-2008

Abstract: BackgroundTick-borne encephalitis (TBE) virus can cause severe symptoms in humans. The incidence of this vector-borne pathogen in humans is characterised by spatial and temporal heterogeneity. To explain the variation in reported human TBE cases per county in southern Germany, we designed a time-lagged, spatially-explicit model that incorporates ecological, environmental, and climatic factors.ResultsWe fitted a logistic regression model to the annual counts of reported human TBE cases in each of 140 counties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 47 publications
2
35
1
4
Order By: Relevance
“…Correspondingly, studies in Sweden, where tick abundance has been studied have found, that the increasing number of ticks can be explained by high availability of tick maintenance hosts, particularly roe deer, which has been increasing in the last three decades and the warmer climate, that influences the growing season, and consequently both the tick and deer [34]. Additionally, studies have confirmed a positive correlation between densities of roe deer and TBE infected ticks and TBE incidence [29], [31], [46], [47].…”
Section: Discussionmentioning
confidence: 92%
“…Correspondingly, studies in Sweden, where tick abundance has been studied have found, that the increasing number of ticks can be explained by high availability of tick maintenance hosts, particularly roe deer, which has been increasing in the last three decades and the warmer climate, that influences the growing season, and consequently both the tick and deer [34]. Additionally, studies have confirmed a positive correlation between densities of roe deer and TBE infected ticks and TBE incidence [29], [31], [46], [47].…”
Section: Discussionmentioning
confidence: 92%
“…In North America, landscape fragmentation seems to play a crucial role in explaining patterns of tick abundance and Lyme Borreliosis prevalence mediated by ungulate and small mammal dynamics [143]. The influence of the landscape context is not yet completely understood in Europe, but there are indications that landscape fragmentation is responsible for patterns of tick-borne encephalitis in European agricultural landscapes [144] and the prevalence of B. burgdorferi in forests and pastures [145]. This is presumably due to the greater amount of edges in fragmented landscapes where small vertebrates, ungulates and medium-sized mammals act as reservoir hosts.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…This method of classification might be misleading because of increasing vaccination rates in humans, particularly in risk areas, and a resulting decrease in the number of human TBE cases. Additionally, the exposure of humans to ticks might vary substantially in space and time and might thus also introduce bias to the current risk-mapping approach (Kiffner et al 2010). Further, humans are accidental hosts rarely becoming infected, and quite often an infection will not be recognized because of unspecific symptoms, mild courses of disease, or unawareness of physicians.…”
Section: Introductionmentioning
confidence: 99%